Kajian Relaktasi Pada Ibu Menyusui - Rahmi Nurrasyidah (Jurnal Medika Cendikia, 2015)
In Indonesia, a target of achieving exclusive breastfeeding was set at 80%. However, in reality, coverage of exclusive breastfeeding in Indonesia decreased. One solution to enhance return with coverage of exclusive breastfeeding is doing relactation. Relactation was an attempt to breastfeed again after so long stop to breastfeed. Relactation can be performed in women who had never breastfed or had never been breast-feeding. This literature study aims to determine the success of relactation and the factors that influence the success of relactation. This study is a review of the literature. The duration of the process of relactation depends on the age of the baby. Factors that influence the success of relactation including galactogues use, the support of her husband and the support of mothers (p <0.05). Mothers who failed in the process of relactation occurs because frustrating with a little milk (43%), fatigue (14.3%), weight infants less (14.3%), flat nipple (14.3%), a strong rejection of infants (4.8%), pregnant (4.8%), and no support from family (4.8%). Research on relactation in Indonesia is very limited. Thus, more research is needed to support the evidence of the success of relactation.